"One Stop Crisis Centres" for the Redress of Sexual Offenses in India: Addressing Gaps between Policy, Execution, and Implementation. (2022) - Agarwal, Sonu; Sharma, Deepankar
Abstract: Women in India have perpetually been the victims of sexual offenses. The data of the National Crime Records Bureau suggests that such offenses against women are prevalent in almost every part of the country. The year 2013 marked major reforms to the legal and judicial structure for addressing these sexual offenses against female victims. It was felt that special support agencies should be established under one roof to administer every kind of assistance these victims require. Victims should not be mandated to run from pillar to post seeking justice from various agencies and institutions; rather, assistance should be made available to them at one location. To aid and assist the victims of sexual offenses, the Justice Usha Mehra Commission of Inquiry 1 was constituted by India's central government just after the horrific gang rape of a medical student in Delhi in 2012. The Commission recommended the establishment of One Stop Crisis Centres (OSCCs) to help victims of sexual offenses with their legal battles against their offenders. But a primary question has loomed about the effectiveness of such Centres on the ground level, given the lack of resources in our criminal justice enforcement system and a strained policing mechanism. This article deliberates on the fundamental contours of roles and responsibilities to be performed by the OSCCs and deep dives into the investigation of factors presumably responsible for their less-than-desirable output, if any.